Aproveitamento de resíduos agrícolas: cladódio de pitaia no tratamento sustentável de água para consumo humano - parte 2 - Carlos, Emili Borges; Ferrarini, Suzana Frighetto; Bortoluzzi, Airton Luiz; Berreta, Márcia dos Santos Ramos; Lara, Daniela Mueller de (Ciência e Natura, 2026)
The growing global challenge of access to safe drinking water highlights the need for sustainable alternatives in water treatment. This study evaluated the potential of pitaya cladode (Hylocereus spp.) as a natural bio-coagulant, comparing it to aluminum sulfate and Moringa oleifera. The methodology involved coagulation tests with varying concentrations and fixed parameters for pH and rapid mixing times, assessing turbidity, apparent color, true color, pH, and Dissolved Organic Carbon (DOC). The results showed that pitaya performed comparably to aluminum sulfate at pH 3, achieving turbidity and apparent color removal rates above 90%, meeting legal standards. At natural pH, pitaya demonstrated efficiency in turbidity removal after filtration, standing out as a promising alternative for less restrictive treatment systems. This study highlights the use of agricultural residues as an innovative and accessible solution for rural communities, contributing to sustainable practices and aligning with the Sustainable Development Goals (SDGs).